PENERAPAN MODEL COPERATIVE LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VII SMP NEGERI 2 DELIMA - Israfiddin (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2018)
This study aims to determine the effectiveness of the implementation of the Cooperative Learning model in improving student learning outcomes. This study uses a Quasi Experimental design through the Matching-Only Pretest-Posttest Control Group Design implemented at SMP Negeri 2 Delima. Sample selection uses a purposive sampling technique, Sample selection uses a purposive sampling technique, which are class VII-c as the experimental class and VII-d as the control class. Data collection is carried out with pretests and posttests to determine the improvement in student learning outcomes. The results of the N-gain test show that the average score of students taught with the Cooperative Learning model has increased by 71% in the high category, while the average score of students taught with conventional learning methods has increased by 36% in the medium category.